Correlation and Taylor scale variability in the interplanetary magnetic field fluctuations as a function of solar wind speed - Weygand, James M. (2011)
Simultaneous multiple point measurements of the magnetic field from 11 spacecraft are employed to determine the correlation scale and the magnetic Taylor microscale of the solar wind as functions of the mean magnetic field direction and solar wind speed. We find that the Taylor scale is independent of direction relative to the mean magnetic field in both the slow (<450 km/s) and the fast (>600 km/s) solar wind, but the Taylor scale is longer along the mean magnetic field direction in the intermediate (600 km/s ≥ speed 450 ≥ km/s) solar wind. The correlation scale, on the other hand, varies with angle from the mean magnetic field direction. In the slow solar wind the ratio of the parallel correlation scale to the perpendicular correlation scale is 2.55 ± 0.76, decreases to 2.15 ± 0.18 in the intermediate solar wind, and becomes 0.71 ± 0.29 in the fast solar wind. Thus, solar wind turbulence is anisotropic, dominated by quasi two-dimensional turbulence in both the slow and intermediate solar wind, and by slab type turbulence in the fast solar wind. The correlation and Taylor scales may be used to estimate effective magnetic Reynolds numbers separately for each angular channel. To within the uncertainty, no dependence on the solid angle relative to the mean magnetic field could be identified for the Reynolds number. These results may be useful in magnetohydrodynamic modeling of the solar wind and can contribute to our understanding of solar and galactic cosmic ray diffusion in the heliosphere. Copyright © 2011 by the American Geophysical Union.